Empowering Communities through Enhancing Environmental Awareness: A Case Study of Cikelat Village, Sukabumi, West Java in Community Service Activities - Aryo De Wibowo Muhammad Sidik; Edwinanto Edwinanto; Adi Padilah; Abdul Hak; Metodiusman Gulo; Gilang Insan Aghniya; Iqbal Tawakal; Mohammad Nashrul Hidayat; Fredy Yusman Alexius Lase; Muhammad Rifki Sofian; Gina Raodotul Jannah; Sinta Apriliani; Nadira Salsabila Oktaviani; Siti Latifah; Septiani Astuti; Ujang Faisal Kusnadi; Moh Ival Alpian S; Putri Erna Oktavia; Indri Aprianti; Siti Nur Annisa; Tiara Azzahra Anzani; Yurikeu Putri Agustin (Journal of Innovation and Community Engagement, 2024)
This article highlights a community service initiative titled "Empowering Communities through Enhancing Environmental Awareness: A Case Study of Cikelat Village, Sukabumi, West Java in Community Service Activities". In response to the pressing need for sustainable development, this project was undertaken with the aim of elevating environmental consciousness within the community. The primary objectives were to foster a deep understanding of environmental issues, instill sustainable practices, and stimulate community participation. Employing a participatory approach, the engagement encompassed workshops, awareness campaigns, and skill-sharing sessions, fostering a sense of ownership among residents. Collaborative partnerships with local stakeholders formed the bedrock of the strategy, promoting shared responsibility. The outcomes revealed a substantial surge in environmental awareness among villagers, leading to the adoption of eco-friendly practices. The success of the initiative underscores the potential of community-driven efforts to drive sustainable development by intertwining environmental consciousness and active engagement.